Colonial Mobility and the Biopolitics of the Colonial Non-Place - Lee, Jinhyoung (Archīum Ateneo, 2024)
By approaching Namcheon Kim’s short story “On the Road” (1939) from the new mobilities paradigm, this paper explores the paradoxical relationship between the colonial government and the postcolonial politics in late colonial Korea. In this short story, the Korean territories in the late 1930s are represented as colonial “non-places,” in which is exercised imperialistic biopower through colonial mobility. The Korean people residing in the non-places are characterized as bare lives on-the-move who only seek to survive, yielding their political rights to the imperialistic biopower. Thereby, this short story demonstrates the reorganization of the colonial territory as a colonial non-place and the transformation of the Korean population into colonial subjects in order to stabilize the Japanese colonial regime. However, considering that the bare lives on-the-move are divested of any identity, relations, and history, the colonial non- place might be construed to be disclosing the vulnerability of the Japanese colonial regime and, thus, the possibility of postcolonial politics.